Brokering Employment Pathways from Supported Employment Settings to the Mainstream Labour Market - Perri Campbell; Andrew Joyce; Erin Wilson; Robyn Eversole; Jenny Crosbie (Disabilities)
In Australia, many people with a disability work in Supported Employment Settings (previously known as Australian Disability Enterprises or ADEs). SESs are in a unique position to provide training and support to people with a disability as a transition step to employment in the mainstream labour market. This paper examines how one case study SES facilitates pathways to open employment for supported employees. We explore three key questions: what do these pathways look like, what role can Supported Employment Settings play in facilitating these transitions, and what are the challenges in doing so? We argue that successful pathways involve SESs and employers working together to create bespoke opportunities tailored to individuals. Through a detailed picture of the actors and relationships that are involved in setting up employment pathways, our findings demonstrate the need for both employee and employer preparation and how this can be carried out through purposeful planning.